THE IMPACT OF PROFITABILITY, LIQUIDITY, LEVERAGE, AND OPERATING CASH FLOW ON FINANCIAL DISTRESS (STUDY ON TRANSPORTATION AND LOGISTICS COMPANIES ON THE IDX FOR THE 2019-2023 PERIOD) - Galih Rizal Maulana; Farida Titik Kristanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study has an objective to evaluate the impact of profitability, cash flow, liquidity, and leverage factors on financial distress, both concurrently and partly. The analysis included all logistics and transportation firms on IDX. The sampling method leverages the purposive sampling means with the criteria: 1) Transportation and logistics firms listed on IDX. 2) Transportation and logistics firms with complete data for the 2019-2023 timeframe using the variables analyzed. 3) Transportation and logistics firms that present the figures in Rupiah. Based on these parameters, 27 samples were collected. This is a causal study that takes a quantitative research technique. This study relies on secondary data of which the form is financial reports. The data analysis approach employed was panel data regression with Eviews software. The output of the study indicates that: 1) Financial distress is impacted by profitability, cash flow, leverage, and liquidity. 2) Profitability has a favorable and considerable impact on financial difficulties. 3) Liquidity has a favorable and large impact on financial distress. 4) Leverage has a negative, considerable impact on financial difficulties. 5) Cash flow has a beneficial but not significant impact on financial distress.